Nanomaterials as photothermal agents for biomedical applications - Cuello, Emma Antonia (2020)
Photothermal therapy (PTT) is a potentially curative treatment modality that in recent years has been the object of growing interest and rapid technological advances due to its specific therapeutic efficacy and because it is a non-invasive technique. Nowadays, several nanomaterials have been developed as photothermal agents including metallic and carbon-based nanoparticles, conducting polymers, and different kinds of nanocomposites, among others. In this article, the most relevant applications of these photothermal nano-agents in antibacterial and anticancer therapy are reviewed.